PENGEMBANGAN MEDIA INTERAKTIF BERBASIS CANVA DENGAN MATERI EKOLOGI DAN PELESTARIAN LINGKUNGAN - Kolengsusu, Haris (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
The aim of the research is to determine the development of interactive media based on the Canva application and determine the validity, practicality and effectiveness of interactive media based on the Canva application with ecological and environmental conservation material. The method used in this research is R&D (Research and Development) with the development of Borg and Gall (2014) and uses the steps of knowledge study, development and results. The development of Canva media in scientific disciplines goes through various stages and revisions, namely the validation stage by experts. media and materials with good scores, namely 100% and 78.12%. With an assessment score from media experts, a score of 89% was obtained. And the results of the educator assessment found an average percentage of 84.42% in the